Assessing the Impact of Women’s Empowerment on their Nutritional Status in Bangladesh: A Multilevel Logistic Regression Analysis - Eva, Mahmuda Khanom; Ema, Nusrat Jahan; Al Mamun, Abu Sayed Md; Hasan, Md Mahmudul; Haque, Md Ahshanul; Kundu, Ramendra Nath; Bharati, Premananda; Hossain, Md Golam (International Journal of Statistical Sciences, 2024)
Women’s empowerment is one of the ten ‘special initiatives’ of Bangladesh government. According to the Global Gender Gap Report 2022, Bangladesh ranks as the most gender-equal nation in South Asia. Understanding how Bangladeshi women are empowering themselves and its impact on their nutritional status is crucial, as the Sustainable Development Goals (SDGs) include both gender equality and women's health. This study aims to investigate women’s empowerment in Bangladesh and its impacts on their nutritional status. A total number of 14,862 samples were extracted from Bangladesh Demographic and Health Survey (BDHS) 2017-18 for this study. Women’s empowerment was measured using three indicators; (i) women’s participation to make decision on their healthcare, (ii) women’s participation to purchase households goods and (iii) person who usually decides to visit family and friends. The composite index of these three indicators was used as outcome variable for further statistical analysis. The study revealed that 79.0%, 76.1% and 78.4% women participated to make decision on their healthcare, purchasing household goods and visit to relatives and friends respectively, resulting in 63.7% women being classified as empowered in Bangladesh. Predictors of women’s empowerment included: living location (division), type of residence, place of delivery, sex of household head, wealth index, respondents’ age, education, occupation, having bank account, total ever born children and decision in using contraception, and beating by husband. After controlling the effect of other factors, it was shown that empowered women were more likely to become over nourished than unempowered women. The study also found that a strikingly large proportion of women in Bangladesh remained unempowered. Some modifiable factors were found as predictors of women empowerment. Additionally, unempowered women were more likely to be undernourished. International Journal of Statistical Sciences, Vol. 24(2), November, 2024, pp 19-34